2019
DOI: 10.1111/cpr.12692
|View full text |Cite
|
Sign up to set email alerts
|

IL‐37b alleviates inflammation in the temporomandibular joint cartilage via IL‐1R8 pathway

Abstract: Objectives Interleukin (IL)‐37 is a natural suppressor of innate inflammation. This study was conducted to explore the anti‐inflammatory effects of IL‐37 in temporomandibular joint (TMJ) inflammation. Materials and Methods The expression of IL‐37 in the TMJ was measured using ELISA and IHC. Human TMJ chondrocytes were treated with IL‐37b and IL‐1β, and inflammation‐related factors were detected. siRNA‐IL‐1R8 was transfected into chondrocytes, and the affected pathways were detected. IL‐37b was used in disc‐per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…However, as described above, IL-37 plays an important anti-inflammatory and immunomodulatory capacity in a variety of inflammatory and autoimmune diseases. In addition, IL-37 in vivo could inhibit NLRP3 activation also be mentioned in colitis and LPS-induced disease [19,22,[35][36][37]. In recent study, Rudloff et al reported that IL-37 significantly suppress inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…However, as described above, IL-37 plays an important anti-inflammatory and immunomodulatory capacity in a variety of inflammatory and autoimmune diseases. In addition, IL-37 in vivo could inhibit NLRP3 activation also be mentioned in colitis and LPS-induced disease [19,22,[35][36][37]. In recent study, Rudloff et al reported that IL-37 significantly suppress inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…However, as described above, IL-37 plays an important anti-inflammatory and immunomodulatory capacity in a variety of inflammatory and autoimmune diseases. In addition, IL-37 in vivo could Stem Cells International inhibit NLRP3 activation also in colitis-and LPS-induced disease [19,22,[35][36][37]. In a recent study, Rudloff et al reported that IL-37 significantly suppresses inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…15,45 Additionally, various joint-derived cell studies, such as synovial fibroblasts, chondrocytes and osteoblasts studies as well, used IL-1β as one of TMJOA stimulators. [46][47][48][49] Thus, we uti- In the present study, the elevation of TLR4 was accompanied by the augmentation of MyD88, NFκB p65 as well as pro-inflammatory and catabolic mediators both in discectomy-induced TMJOA mice and in IL-1β-induced chondrocytes, and vice versa. Although these findings cannot illustrate the explicit mechanism that how TLR4 manipulates TMJOA progression, it is strongly indicated that TLR4 contributes to the damage of cartilage and subchondral bone during TMJOA progression through activation of MyD88/NFκB to release the pro-inflammatory and catabolic mediators, as the role of TLR4/ MyD88/NFκB signal pathway in regulating inflammatory mediators has been specified in varied diseases.…”
Section: Discussionsupporting
confidence: 50%
“…The abundance of IL‐1β in joint is a striking feature of TMJOA development 15,45 . Additionally, various joint‐derived cell studies, such as synovial fibroblasts, chondrocytes and osteoblasts studies as well, used IL‐1β as one of TMJOA stimulators 46‐49 . Thus, we utilized IL‐1β stimulating chondrocytes to mimic TMJOA condition in vitro.…”
Section: Discussionmentioning
confidence: 99%